Sharpening the Sword of State - Podger, Andrew; Wanna, John (ANU Press, 2016)
Sharpening the Sword of State explores the various ways in which 10 jurisdictions in the Asia-Pacific enhance their administrative capabilities through training and executive development. It traces how modern governments across this region look to develop their public services and public sector organisations in the face of rapid global change. For many governments there is a delicate balance between the public interest in promoting change and capacity enhancement across the public service, and the temptation to micro-manage agencies and be complacent about challenging the status quo. There is a recognition in the countries studied that training and executive development is a crucial investment in human capital but is also couched in a much wider context of public service recruitment, patterns of entry and retention, promotion, executive appointment and career development. This empirical volume, authored by academics and practitioners, is one of the first to chart these comparative differences and provide fresh perspectives to enable learning from international experiences